2020
DOI: 10.1002/ajcp.12437
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Tendencies, Big 5 Personality Traits, and Self‐Efficacy as Predictors of Mentors’ Relationships with Aggressive Children

Abstract: Highlights It is important for programs to identify those mentor characteristics that predict match quality. Attachment tendencies, personality traits, and self‐efficacy were examined in this study. These characteristics differentially predicted match quality for mentors of aggressive children. Openness and avoidant attachment positively and negatively predicted match quality, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
1
10
2
Order By: Relevance
“…We also did not find evidence to support hypothesis two-neither mentor Anxious nor Avoidant attachment was associated with mentoring relationship quality. Thus, we did not replicate the findings from Cavell et al (2020) that mentor Openness to Experience is associated with mentor perceptions of more positive relationship outcomes, and mentor Avoidant attachment style is associated with mentor perceptions of negative relationship outcomes.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…We also did not find evidence to support hypothesis two-neither mentor Anxious nor Avoidant attachment was associated with mentoring relationship quality. Thus, we did not replicate the findings from Cavell et al (2020) that mentor Openness to Experience is associated with mentor perceptions of more positive relationship outcomes, and mentor Avoidant attachment style is associated with mentor perceptions of negative relationship outcomes.…”
Section: Discussioncontrasting
confidence: 85%
“…In regard to mentor personality traits specifically, in a sample of college-age mentors working with aggressive, elementary school children, Faith et al (2011) found mentors who perceived their relationships as supportive experienced increases in the personality dimensions of Agreeableness, Conscientiousness, and Extraversion. In a more recent study, Cavell et al (2020) found evidence that mentors' scores on the Big Five dimension of Openness were positively associated with mentor perceptions of match quality while controlling for other personality dimensions and mentor attachment. Mentor personality was not associated with child-report of match quality in this study.…”
Section: Mentor Personality Tendencies As a Predictor Of Relationship Qualitymentioning
confidence: 96%
See 3 more Smart Citations